Validation of a novel questionnaire for assessing occupational exposure to organophosphate pesticides in Chilean agricultural workers - Zúñiga-Venegas, Liliana; Landeros, Natalia; Pancetti, Floria; Cortés, Sandra; Lucero, Boris; Brito, Ana M.; Acuña-Rodríguez, Ian S.; Muñoz-Quezada, María Teresa (Frontiers in Toxicology, 2025)
BackgroundUnintentional pesticide poisoning is a global health concern, disproportionately affecting agricultural workers in developing countries due to inadequate regulations and limited access to protective equipment. While questionnaires offer a cost-effective alternative for assessing organophosphate (OP) pesticide exposure compared to urinary (e.g., Dialkyl Phosphates, DAPs) or blood biomarkers (e.g., acetylcholinesterase, AChE, and butyrylcholinesterase, BChE), these tools require validation against gold-standard methods. This study validated a questionnaire assessing occupational OP exposure among Chilean agricultural workers in the Maule region, contrasting its performance against DAP levels and AChE and BChE inhibition.MethodsA longitudinal study was conducted with 51 agricultural workers. Urinary DAPs, measured via liquid chromatography–tandem mass spectrometry, AChE, and BChE activities, determined by Ellman’s method, were measured before (T0) and during (T1) the spray season. The questionnaire was administered at T1. Sensitivity, specificity, predictive values, and Receiver Operating Characteristic (ROC) curve analyses were performed to assess the accuracy.ResultsUrinary DAP levels and AChE inhibition increased in T1 (from 6.54 ± 4.66 to 12.39 ± 9.88 μg/g creatinine, p = 0.004, and from 2.26E-3±6.53E-4 to 1.44E-3±2.73E-4 mmol/min-1*mgProt-1, p < 0.001, respectively), with AChE inhibition (30.99%) exceeding Chilean regulatory threshold. The questionnaire score correlated with AChE inhibition (p = 0.0063) but not with BChE inhibition or DAP levels. Sensitivity was 64%, and specificity improved from 56% to 71% when using a 20% AChE inhibition threshold instead of a 30%.ConclusionAgricultural workers in the Maule region are exposed to OP pesticides. The questionnaire shows potential as a screening tool for occupational exposure. These findings highlight the need to reassess the Chilean regulatory limits and refine the tool to enhance risk assessment and intervention planning.